Pulmonary Alveolar Proteinosis in Association with Congenital Dyserythropoietic Anemia: A Case Report - Marcus A. Carden; Ashish Barman; Gita Massey (Case Reports in Pediatrics)
A two-year-old girl with congenital dyserythropoietic anemia (CDA) acutely developed fever, tachypnea, and increased oxygen requirement. Chest X-ray revealed bilateral interstitial infiltrates and mild cardiomegaly. Blood cultures grew no infectious agents, while pulmonary specimens grew cytomegalovirus (CMV). Treatment with intravenous ganciclovir was initiated but without response. Final cytologic preparations of bronchoalveolar lavage (BAL) fluid revealed eosinophilic amorphous material consistent with pulmonary alveolar proteinosis (PAP). CDA and PAP are extremely rare disorders in pediatrics. PAP should be considered in patients with hematological disorders who present with acute interstitial pneumonia, after infectious causes are ruled out.